GPS : a matemática por trás e algumas reflexões - Souza, Joel Cordeiro de (2021)
This master’s thesis presents the mathematical principles behind the operation of the global positioning system called GPS. There will be seen a historical approach that reveals the evolution of the means of location until the arrival of this technology. In order to understand how the mathematics used in GPS is developed there are multiple components that must be grasped, such as flat, spatial and analytic geometry. Some basic physical principles will be mentioned, such as average speed, speed of light and Doppler effect. The focus will be on some definitions like latitude, longitude and altitude to understand how this system can accurately locate people, vehicles or anything, just having a GPS receiver. In addition, it will be discussed that, underlying and associated with GPS technology, there are several and very serious problems, especially in what has come to be called uberization of work. Workers in a miserable situation, without a fixed salary, without labor rights, without protection, making use of the latest technology to work. And from there, some interdisciplinary activities are proposed to be developed in basic education, in order to arouse students’ curiosity about the scientific knowledge contained therein.